PROSES INISIASI PERILAKU SEKS PRANIKAH PADA MAHASISWA DI KOTA SEMARANG - Kismi Mubarokah (Jurnal Berkala Kesehatan, 2015)
Abstract Epidemic HIV/AIDS in Indonesia is still high. The high risk factor comes from sexual transmission. Based on previous survey, 77, 1% young adult in Semarang involve risky sexual behavior. To describe the initiation process of sexual behavior before married in university students.The research used qualitative approach. The participants are university student in Semarang City and have experienced in sexual intercourse (heterosexual). From eight participants involved, most of sexual behavior occurs without intention. Initiation of sexual behavior begins with discussing about sexuality between close friends in enclosed place. This initiation makes them to continue to do sexual intercourse. Adolescence should involve in formal group discussion about sexual and reproductive topic to encourage them to responsible sexual behavior. Keywords: intention, sex behavior, initiation, attitude